The N = 1 Triplet Vertex Operator Superalgebras: Twisted Sector - Adamovic, D.; Milas, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We classify irreducible σ-twisted modules for the N = 1 super triplet vertex operator superalgebra SW(m) introduced recently [Adamovic D., Milas A., Comm. Math. Phys., to appear, arXiv:0712.0379]. Irreducible graded dimensions of σ-twisted modules are also determined. These results, combined with our previous work in the untwisted case, show that the SL(2,Z)-closure of the space spanned by irreducible characters, irreducible supercharacters and σ-twisted irreducible characters is (9m + 3)-dimensional. We present strong evidence that this is also the (full) space of generalized characters for SW(m). We are also able to relate irreducible SW(m) characters to characters for the triplet vertex algebra W(2m + 1), studied in [Adamovic D., Milas A., Adv. Math. 217 (2008), 2664-2699, arXiv:0707.1857].